Parental utilisation of child medical care : a grounded theory approach : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University - Martin, Melanie F. (Massey University, 2002)
Within New Zealand, child medical care use is a prevalent source of concern with current medical care utilisation rates considered inadequate to achieve optimal child health. Although previous research into child medical care use has made a valuable contribution to understanding in this area, such research is plagued by various limitations that indicate the need for further research adopting a different approach. This study draws on a social constructionist perspective and grounded theory methods to investigate parents' talk surrounding child medical care use. The study investigates how parents construct their seeking treatment and prevention of childhood illness and disease from a medical practitioner or nurse looking at, in particular, seeking medical treatment for childhood illness, the use of Well Child checks, and childhood immunization. Individual semi-structured interviews were conducted to explore how parents construct the complex process of child medical care use. The findings indicate that child medical care use, in the form of treatment-seeking and the utilisation of Well Child services, is constructed as two distinct but similar processes. Generally, the findings demonstrate that such child medical care use comprises parents constantly negotiating various issues and concerns characterised by tension, conflict, and dilemma. These issues and concerns consist of doing the 'right' thing, the risk of medicines and immunisations, practical barriers to seeking care, competing demands and priorities, and social expectations and social pressure. These issues and concerns arise - and are resolved - within the wider context of parents trying to be 'good parents', trying to preserve child health (not just treat illness), the immediate environment surrounding treatment-seeking, parents trying to fulfil social roles - and individual and socially shared understandings of, for example, medicines. More broadly, child medical care use is conceptualised as a socially based decision-making process that takes place within a social context in which child health, illness, and disease are medicalised, and within which parents are trying to do the right thing for the child. The findings from this study contribute to knowledge and understanding in this area in a number of ways. These are discussed, along with the implications of these findings, and recommendations for future research are made.
Irregular pagination: missing page v
Keywords: Child health; Child health care; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology